Prevalence and risk factors of dysnatremia in sick newborns admitted in neonatal intensive care unit: a cross-sectional study - Hassan, Farogh; Kumar, Vasanth N.; Asghar, Imran; Jha, Lata; Choudhury, Indranil (International Journal of Contemporary Pediatrics, 2020)
Background: The objective of the study was to study the prevalence and various risk factors of dysnatremia in sick newborns admitted in neonatal intensive care unit (NICU). Methods: Cross sectional study conducted in Paediatric Department of tertiary care hospital from February 2016 to October 2016 which includes 384 neonates admitted to NICU during the study period. After informed consent, detailed history was taken and clinical examination carried out in both cases and controls. Blood investigations were done to diagnose sodium levels in sick neonates. Based on the corrected sodium values, the subjects were classified as having hyponatremia (serum sodium <135 meq/l), hypernatremia (serum sodium >145 meq/l) or normonatremia (serum sodium 135 to 145 meq/l). Results: The mean (SD) (range) serum sodium in sick newborns measured was 136.72 (6.7) (115-165) meq/l at a median (range) age of 56.97 (1-545) hours. Out of 384 sodium values obtained, 285 (74.2%) were sent on ≤3 days, 64 (16.7%) between 4th to the 6th day and 35 (9.1%) were sent on ≥7 days. The overall frequency of dysnatremia in 384 sodium values from 384 patients was 142 (37%). Hyponatremia was observed in 117 (30.5%) and hypernatremia in 25 (6.5%) of sodium values. Hyponatremia observed in term, low birth weight, very low birth weight and extremely low birth weight neonates were 16.4%, 25.2%, 67.2% and 100% respectively whereas hypernatremia were 10.1%, 4.6%, 3.4% and 0% respectively. Various risk factors for hyponatremia namely; prematurity, necrotizing enterocolitis, renal failure, birth asphyxia, sepsis, meningitis, vomiting/ nasogastric drainage. Conclusions: Hyponatremia are common in sick newborns in NICU.